Fungal Diseases in Pistachio Production: Analyzing Their Impact and Exploring Sustainable Solutions Amidst Environmental and Biological Influences - Odina Nazarova; Khujaev Otabek (Genius Journals, 2025)
Fungal pathogens pose a significant challenge to pistachio production by affecting both yield and nut quality. This paper examines the multifaceted impact of major fungal diseases—such as Aspergillus flavus, Verticillium dahliae, and Phytophthora spp.—on pistachio orchards, with a focus on environmental, biological, and agronomic influences. Climate change, particularly increased temperatures and altered precipitation patterns, is shown to intensify fungal proliferation and mycotoxin production, thus heightening health and economic risks. Furthermore, soil salinity and microbial interactions significantly affect tree susceptibility and disease dynamics. The paper highlights promising sustainable control strategies, including integrated pest management (IPM), the application of biocontrol agents like Trichoderma spp., use of micronutrients and plant growth regulators, and promotion of microbial diversity in the rhizosphere. Emphasis is placed on a holistic approach that combines biological control, soil health improvement, and climate-adapted practices to enhance pistachio resilience. The findings underscore the need for eco-friendly, multi-dimensional management strategies to ensure the long-term sustainability of pistachio cultivation under increasing environmental stress
Keywords: Fungal diseases; Aspergillus flavus; Verticillium dahliae